Flavonoids as a Natural Enhancer of Neuroplasticity-An Overview of the Mechanism of Neurorestorative Action - Natalia Cichon; Joanna Saluk-Bijak; Leslaw Gorniak; Lukasz Przyslo; Michal Bijak (MDPI AG, 2020)
Neuroplasticity is a complex physiological process occurring in the brain for its entire life. However, it is of particular importance in the case of central nervous system (CNS) disorders. Neurological recovery largely depends on the ability to reestablish the structural and functional organization of neurovascular networks, which must be pharmacologically supported. For this reason, new forms of therapy are constantly being sought. Including adjuvant therapies in standard treatment may support the enhancement of repair processes and restore impaired brain functions. The common hallmark of nerve tissue damage is increased by oxidative stress and inflammation. Thus, the studies on flavonoids with strong antioxidant and anti-inflammatory properties as a potential application in neuro intervention have been carried out for a long time. However, recent results have revealed another important property of these compounds in CNS therapy. Flavonoids possess neuroprotective activity, and promote synaptogenesis and neurogenesis, by, among other means, inhibiting oxidative stress and neuroinflammation. This paper presents an overview of the latest knowledge on the impact of flavonoids on the plasticity processes of the brain, taking into account the molecular basis of their activity.